2017
DOI: 10.1038/srep42554
|View full text |Cite
|
Sign up to set email alerts
|

Nanomechanical effects of light unveil photons momentum in medium

Abstract: Precision measurement on momentum transfer between light and fluid interface has many implications including resolving the intriguing nature of photons momentum in a medium. For example, the existence of Abraham pressure of light under specific experimental configuration and the predictions of Chau-Amperian formalism of optical momentum for TE and TM polarizations remain untested. Here, we quantitatively and cleanly measure nanomehanical dynamics of water surface excited by radiation pressure of a laser beam. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 25 publications
1
2
0
Order By: Relevance
“…In recent years, with the development of microstructural deformation measurement technology, together with numerical simulations, some scholars have measured the gas-liquid interface deformation caused by light pressure at the nanoscale and carried out numerical simulation based on theoretical models. The results are in good agreement with Minkowski momentum [10][11][12][13]. However, similar experiments conducted by Zhang and She et al after changing the experimental parameters showed the sunken of the gas-liquid interface caused by light pressure, thus supporting the Abraham momentum [14].…”
Section: Historysupporting
confidence: 84%
“…In recent years, with the development of microstructural deformation measurement technology, together with numerical simulations, some scholars have measured the gas-liquid interface deformation caused by light pressure at the nanoscale and carried out numerical simulation based on theoretical models. The results are in good agreement with Minkowski momentum [10][11][12][13]. However, similar experiments conducted by Zhang and She et al after changing the experimental parameters showed the sunken of the gas-liquid interface caused by light pressure, thus supporting the Abraham momentum [14].…”
Section: Historysupporting
confidence: 84%
“…The canonical (Minkowski) momentum is related to the idea of translations within, or relative to, a host medium and to the wavelength of light, explaining the immersed mirror experiment and wavelike phenomena such as diffraction. However, interpreting the manifestations of photon momentum transfer remains problematic [7,[11][12][13][14][15][16][17].…”
mentioning
confidence: 99%
“…[35,39] The fringe pattern was self-calibrating for nanoscale measurements and has been used as a direct measurement of laser-induced deformation of the AW interface. [35,40,41] To measure the spatial profile of the AW interface, keeping the pump beam fixed, we scanned the probe beam across the AW interface by translating the mirror M3 (Figure 1a).…”
Section: Resultsmentioning
confidence: 99%